POTENSI INFUSA DAUN SIRSAK (Annona muricata L.) TERHADAP KADAR KOLESTEROL DARAH TIKUS PUTIH JANTAN (Rattus novergicus) - Uneputty, Jonly Piere; Yamlean, Paulina V. Y.; Kojong, Novel (PHARMACON, 2013)
The objectives of this study is to decrease blood cholesterol levels from white male rats(Rattus novergicus L.) after giving infusion of soursop leaf (Annona muricata L). This studyused experimental laboratory method with complete randomized design. The subject of thisstudy are 15 white male rats weigth 100-160 gramme which were divided into 5 groups, 3rats for each group. The results were taken from 2 times measurement of blood cholesterolwhich are pre-test and post-test. Treatment began with a high-fat feeding for 7 days. The pretestwas done at 8th day. Then each group were given treatment, group A (C-) was givenaquadest, group B (C+) was given simvastatin and group C-E was given infusion of soursopleaf which each dose is 3, 5,and 10 soursop leaf. The post-test was done at 12 hours. Datawere analyzed by using ANOVA one way. The results of statistical analysis didn’t havesignificant differences between treatment groups. But consider from the average change,infusion dose of 5 soursop leaf gives the best decrease of blood choleterol levels.Key words: Blood cholesterol levels, infusion of soursop leaf, white male rats.